Study on the impact of natural graphite amount and dispersion on the electrical performance of PET/graphite composites - Pramono, Agus Edy; Dewi, Anissa Puspa; Nufus, Tatun Hayatun; Indayaningsih, Nanik (Politeknik Negeri Lhokseumawe, 2025)
Polymer composites have experienced rapid development in recent decades due to their ability to integrate mechanical, thermal, and electrical properties tailored for specific applications. One of the major challenges in polymer development is improving electrical conductivity, as most polymers are inherently insulating. To address this, various conductive fillers such as carbon black, graphite, carbon nanotubes, and graphene have been utilized. This study investigates the effect of natural graphite loading on the electrical conductivity, microstructure, and porosity of virgin Polyethylene Terephthalate (PET) composites. Composites containing 10%, 20%, and 30% graphite by weight were fabricated using the hot compaction method. Morphological analysis via Scanning Electron Microscopy (SEM) revealed that higher graphite content enhances filler connectivity, with the formation of conductive pathways beginning at 20% and a continuous network forming at 30%, despite some agglomeration and weak interfacial bonding. Density measurements and porosity analysis indicated that increasing graphite content leads to greater porosity, with the 30% composite reaching 19.68%. Electrical conductivity increased significantly with increasing graphite loading, exhibiting a transition from insulating to conductive behavior. The percolation threshold was identified at approximately 13.2 wt%, with conductivity rising from 0.00347 S/m at 10 wt% to 6.97 S/m at 30 wt%, consistent with classical percolation theory. These findings demonstrate that natural graphite is an effective conductive filler for PET-based composites and that its content must be optimized to balance conductivity with structural integrity.